2017
DOI: 10.1371/journal.pone.0184375
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vital dyes on human corneal endothelium and elasticity of Descemet’s membrane

Abstract: The purpose of this study was to evaluate the effects of vital dyes on human Descemet's membranes (DMs) and endothelia. DMs of 25 human cadaveric corneas with research consent were treated with dyes routinely used in Descemet membrane endothelial keratoplasty (DMEK), 0.05% Trypan blue (TB) or a combination of 0.15% Trypan blue, 0.025% Brilliant blue and 4% Polyethylene glycol (commercial name Membrane Blue Dual; MB). The effects of these two dyes on (i) endothelial cell viability, (ii) DM mechanical properties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…82 Nevertheless, the exposure of the DMEK grafts to these vital dyes should be restricted as studies have reported timedependent toxic effects of these dyes to the CE. 83 To prevent iatrogenic graft failure caused by an inadvertent 'up-side-down' graft, intraoperative orientation of the DMEK graft is essential. 84 However, graft orientation can often be difficult following the intracameral transfer of the graft.…”
Section: Donor Graft Harvestingmentioning
confidence: 99%
See 1 more Smart Citation
“…82 Nevertheless, the exposure of the DMEK grafts to these vital dyes should be restricted as studies have reported timedependent toxic effects of these dyes to the CE. 83 To prevent iatrogenic graft failure caused by an inadvertent 'up-side-down' graft, intraoperative orientation of the DMEK graft is essential. 84 However, graft orientation can often be difficult following the intracameral transfer of the graft.…”
Section: Donor Graft Harvestingmentioning
confidence: 99%
“… 82 Nevertheless, the exposure of the DMEK grafts to these vital dyes should be restricted as studies have reported time-dependent toxic effects of these dyes to the CE. 83 …”
Section: Endothelial Keratoplasty: Current Approachesmentioning
confidence: 99%
“… 29 At the same time, treating of DM tissue with the higher concentration of 0.15% trypan blue (MembraneBlue ® , DORC International, Zuidland, The Netherlands), typically used for vitreoretinal surgery, up to 3–4 minutes led to a deeper blue stain for a prolonged period without detrimental effects on endothelial cell viability. 29 , 30 However, a longer staining time of 5 minutes with 0.15% concentration resulted in a decrease in ECD, approaching statistical significance. 29 In general, a DMEK graft is clinically stained with 0.06% trypan blue for about 30 seconds to 5 minutes before transplantation.…”
Section: Discussionmentioning
confidence: 91%
“…Regarding the concentration and exposure time of trypan blue and ECL, there have been a few in vitro studies attempting to determine the proper concentration and the duration of application of trypan blue dye to DMEK donor corneal tissue to enhance visibility while minimizing endothelial toxicity. 29 , 30 Staining DM grafts with 0.06% trypan blue (VisionBlue ® , DORC International, Zuidland, The Netherlands), which is often used in DMEK, up to 5 minutes was found to be effective and safe. 29 At the same time, treating of DM tissue with the higher concentration of 0.15% trypan blue (MembraneBlue ® , DORC International, Zuidland, The Netherlands), typically used for vitreoretinal surgery, up to 3–4 minutes led to a deeper blue stain for a prolonged period without detrimental effects on endothelial cell viability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation